Feasibility study of rainwater harvesting in Seksyen 7 Shah Alam Selangor / Siti Nor Baizura Abdul Rahman - Abdul Rahman, Siti Nor Baizura (2005)
In Malaysia, there are many trials conducted on rainwater harvesting system in housing projects following the major drought in 1998 that affected the Klang valley, the heart of commercial and industrial areas. The research on rainwater harvesting system to fulfill part of the demand of household is still at its earlier stages. The objective of this study is to investigate the feasibility of using rainwater as non- potable domestic water sources. The method is based on surveying. The surveying based on questionnaire is conducted to obtain the non-potable water usage in residential area. The other surveying is conduct to obtain the cost of the rainwater system. From that, the water usage and volume of rainfall can be obtained. As the conclusion, the objective based on the volume is achieving to implement this system. Even though the objective based on the cost is not achieving because cost from respondent is not adequate to implement this rainwater system.